2022
DOI: 10.1002/eap.2650
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential for demographic restoration and assisted evolution to build climate resilience in coral reefs

Abstract: Interest is growing in developing conservation strategies to restore and maintain coral reef ecosystems in the face of mounting anthropogenic stressors, particularly climate warming and associated mass bleaching events. One such approach is to propagate coral colonies ex situ and transplant them to degraded reef areas to augment habitat for reef-dependent fauna, prevent colonization from spatial competitors, and enhance coral reproductive output. In addition to such "demographic restoration" efforts, manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…Such small‐scale patterns could be generated by low larval movement and also by selection for larvae produced by local parents. These processes have been incorporated into recent models of coral adaptation in the face of climate change (e.g., DeFilippo et al, 2022 ; McManus et al, 2020 ) but such data are not often collected in traditional analyses of coral population genetics (Sheets et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such small‐scale patterns could be generated by low larval movement and also by selection for larvae produced by local parents. These processes have been incorporated into recent models of coral adaptation in the face of climate change (e.g., DeFilippo et al, 2022 ; McManus et al, 2020 ) but such data are not often collected in traditional analyses of coral population genetics (Sheets et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Matz et al ( 2020 ) developed an Indo‐West Pacific model of adaptation based on the migration models of Treml et al ( 2012 ) and showed the possibility of long‐term adaptation across ocean‐wide environmental gradients. At a more local level, McManus et al ( 2020 ) and DeFilippo et al ( 2022 ) used stepping stone models with about 20% recruitment back to the natal reef and showed that wider dispersal spreads locally adaptive alleles but slows potential local increases in adaptive traits such as heat resistance. These models suggest a critical importance of the spatial scales over which natural selection increases allele frequencies to generate successful response to climate (Matz et al, 2020 ), and the scales over which assisted gene flow to accelerate that response will be most valuable (McManus et al, 2020 ; Quigley et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, for some coral species with limited environmental tolerances, aquaculture may serve as a critical tool for their preservation in aquariums and land-based facilities (Schopmeyer et al, 2012;Zoccola et al, 2020). Thus, while the culture of corals has contributed to reef restoration and been used to prevent loss of certain species, little is known about its efficacy when used with a range of coral species and at larger spatial scales, especially with respect to how aquaculture methods may be used to contribute to reef resilience (DeFilippo et al, 2022;Shaver et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term survival of restored corals is predicted to be low if environmental stressors are not alleviated 9 . Outplanting efforts that do not consider integrating coral resistance and resilience to future stressors will therefore produce communities with low likelihood of future survival 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%